Cause-related marketing : will religious consumers buy? - Suzana Md Samsudi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
To meet the UN Sustainable Consumption and Production goal, more companies are integrating sustainability value through corporate social responsibility (CSR) activities as part of their marketing strategies. To highlight the CSR activities and sustainable development, the marketing strategies may change the focus from consumer to social framework such as from customer price discounts to corporate sponsorship or cause-related marketing (CRM). The question remains whether sponsorship or CRM carried out by corporate are perceived as being more socially responsible especially by the religious consumers. This study assesses the influence of religiosity on attitude towards CRM and purchase intention for brands supporting religious, social or environmental causes. A conceptual model with a multi-dimensional construct of religiosity was developed to examine the relationship between religiosity and attitudes towards CRM and purchase intent. A survey among young Muslim adults in Malaysia was carried out to test the influence of religiosity on CRM and purchase intention. The results revealed contradicting support between intra- and inter-personal religiosity. Theoretically, the findings warrant additional research that focuses on the multi-dimensional construct of religiosity and its linkage to CRM as an incentive mechanism. While CRM activities are viewed positively by those who are religious in a more socially manner, those who are inwardly religious however, may reject and perceive the marketing approach negatively.